O papel das maquilas no desenvolvimento do Paraguai: Impactos, oportunidades e desafios - Luiz Marcelo Michelon Zardo; Rafael de Moraes Baldrighi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– The maquila regime in Paraguay has become one of the main drivers of industrial exports of the country. Since its regulation by Decree no 9,585/2000, maquilas have grown significantly, representing 67% of Paraguay's manufactured exports in 2023. Paraguay follows a path similar to other maquiladora experiences in Mexico and Southeast Asian countries, combining tax incentives, affordable labor, and proximity to major consumer markets. In this context, the present article analyzes the evolution of Paraguayan maquilas, their impacts on the national economy, and future challenges and opportunities. The research is based on legal documents, official reports, and statements from Paraguayan authorities. The main conclusions indicate that the maquila regime has played an important role in the industrialization and strengthening of the formal labor market over the last two decades, with particular emphasis during the Cartes government (2013-2018). However, in addition to the low technological intensity, geographic concentration in border regions, and excessive dependence on Mercosur markets, a major challenge to be overcome is the fact that the attractiveness of the regime is still largely based on cost and tax differentials, rather than on more solid and long-term foundations. Finally, regarding the constitution of more sustainable competitive advantages, it is essential to expand Paraguay's participation in extraregional production chains and strengthen its integration with neighboring countries through projects such as the Bioceanic Road Corridor.
Keywords: F15; L52; O14; O24; O25; 330; maquilas; industrial policy; paraguay; global value chains; regional integration